End stage renal disease patients on haemodialysis profiled epidemiologically at medical college of sub-Himalayan region of India - gupta, Pankaj Kumar; Kumar, Dinesh (International Journal of Research in Medical Sciences, 2019)
Background: Mostly, end organ damage becomes the reason for morbidity and mortality among patients with non-communicable diseases (NCDs) due their chronicity. Derangement of renal function along with brain and heart damage are considered to be a significant problem of NCDs. The objectives of this study were on this background of end stage renal disease (ESRD) as a common complication for common NCDs, present study was planned to study the distribution of responsible NCDs. Methods: Over three-year period, all the cases reported GFR <15ml/min/1.73m2 were studied. Results: Total 100 patients (male:65) were studied with mean age of 51.0±13.0 years. Diabetes mellitus (38.0%), hypertension (28.0%), and glomerulonephritis (16.0%) were three leading cause for ESRD. Idiopathic cause was observed among 12.0% patients. Fifteen percent patients could not survive. Conclusions: NCDs mainly diabetes mellitus and hypertension observed to be most common cause for ESRD.